Human Interaction with Nature: Ritus and Forests of the Himalayas - Paudel, Shankar (KMC Research Journal, 2021)
The pivotal concern of my research is to explore the ranges of human interaction with forests and rivers in six different Ritus2 (seasons) in the context of Nepal in general and Morang and Chitwan Districts in particular. People are constantly engaged in various kinds of contact with nature according to the changing seasons. On one level, it is the interaction that occurs between any life form and nature. And on the other hand, especially in the case of humans, it extends towards the variety of causes, i.e. political, religious, and economic/ educational, that shape the interactions between humans and nature. My research aims to explore the nuances of those dialogues between humans and forests that are shaped by natural forces and the religious, socio-economic, aesthetic and common reasons during different Ritus.